Epilepsy care pathway : The Finnish model - Kälviäinen, Reetta; Hadj‐Allal, Zakarya; Kirjavainen, Jarkko; Roivainen, Reina; Linnankivi, Tarja; Peltola, Jukka; Eriksson, Kai; Lamusuo, Salla; Lähdesmäki, Tuire; Annunen, Johanna; Vieira, Päivi; Tarkiainen, Virpi; et al. (Wiley, 2025)
Heterozygous de novo loss of function variants in the motor domain of KIF5C are associated with a neurodevelopmental disorder characterized by infantile-onset epilepsy, frontal cortical dysplasia, and developmental delays including motor and speech impairments. Previously, only three missense variants in KIF5C were known to be pathogenic. We identified an additional six patients with significant developmental delays with heterozygous de novo variants in the KIF5C gene (Glu237Val, Thr93Ile, Thr93Asn, Ser90del, Lys92Arg, and Glu237Lys), of which four variants have not been reported before. Functional assessment was performed on fluorescently-tagged KIF5C variants expressed in isolated hippocampal neurons. The pathogenic de novo variants displayed significantly reduced motor function compared to the wild-type KIF5C. We conclude that the pathogenic de novo variants presented have decreased motor domain activity and that is likely to be the etiology of the patients' symptoms given the gene's constraint in the population. By adding these patients to the seven patients previously reported, we are able to expand the phenotypic spectrum associated with pathogenic KIF5C variants. Evaluation of the neurodevelopmental phenotype of additional individuals with loss of function variants in KIF5C is indicated to further characterize the spectrum of associated phenotypes.